2011
DOI: 10.1016/s0034-7094(11)70029-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Pain

Abstract: Cytokines have an important role in pain through different mechanisms in several sites of pain transmission pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 35 publications
0
83
1
5
Order By: Relevance
“…High NO levels can be cytotoxic [Marcus et al, 2003]. Cytokines cause glial cell hypertrophy and prolif- eration, and release related proinflammatory cytokines, e.g., IL-1β, TNF-α, and IL-6, forming a network of autonomous activation [De Oliviera et al, 2011]. Recently, Zhu et al [2016] observed increased levels of cytokines and GFAP in the hippocampus of rats showing tibial fractures; this inflammatory cascade leads to postoperative neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…High NO levels can be cytotoxic [Marcus et al, 2003]. Cytokines cause glial cell hypertrophy and prolif- eration, and release related proinflammatory cytokines, e.g., IL-1β, TNF-α, and IL-6, forming a network of autonomous activation [De Oliviera et al, 2011]. Recently, Zhu et al [2016] observed increased levels of cytokines and GFAP in the hippocampus of rats showing tibial fractures; this inflammatory cascade leads to postoperative neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NGF acts through posttranscriptional regulation of receptors and ion channels inducing mechanical and thermal hyperalgesia. 25 In summary, there are several positive During inflammation, several mediators directly or indirectly induce pain including pro-inflammatory cytokines and there is evidence that the JAK-STAT pathway is involved in the formation of pronociceptive cytokines. The same pathway, however, is also of importance for anti-inflammatory cytokines such as iL-4 to counteract the inflammatory reaction and-as it seems based on the current literature-nociceptive symptoms.…”
Section: Pain and Inflammationmentioning
confidence: 99%
“…However, extent of surgical resection was not significantly associated with reduction of inflammation. It is also possible that physical discomfort and or pain associated with the tumor mass and/or ascites may have affected inflammatory pathways and functional outcome measures independently (De Jongh et al 2006;de Oliveira, Sakata, Issy, Gerola, & Salomão 2011). Because the current study does not include substantive measures of pain we were unable to examine the relationship of pain with variables of interest.…”
Section: Discussionmentioning
confidence: 89%